2022
DOI: 10.1530/rem-22-0009
|View full text |Cite
|
Sign up to set email alerts
|

Circulating oxysterols in Alzheimer’s disease: a systematic review and meta-analysis

Abstract: Despite decades of research, the cause and series of events underlying the advancement of Alzheimer’s disease (AD) has not yet been established. Lipids and especially cholesterol levels have been proposed to be implicated in AD. Several studies have been undertaken and many ongoing in different directions looking at the importance of circulating cholesterols and oxidised cholesterols in Alzheimer’s disease with inconsistent methods and results. This meta-analysis aims to systematically analyse available data d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…The associations between less favorable lipids and higher 24-OHC and 27-OHC are consistent with some of the literature, 6,9,19,20,21,44 although a recent meta-analysis of case-control studies reported no differences in 24-OHC between MCI (n = 260) or AD (n = 509) patients and controls (n = 438 and n = 428, respectively). 8 Higher dementia risk observed in those with a higher 24-OHC/27-OHC ratio is in agreement with the marginally significant findings of increased cognitive impairment risk reported by Hughes et al, but, in contrast, we did not observe a relationship between 24-OHC levels and dementia risk in our exclusively female sample. 45 Nonetheless, our study is the first to report significantly greater dementia risk in relation to higher 24-OHC/27-OHC, and specifically in APOE3 and APOE4+ carriers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The associations between less favorable lipids and higher 24-OHC and 27-OHC are consistent with some of the literature, 6,9,19,20,21,44 although a recent meta-analysis of case-control studies reported no differences in 24-OHC between MCI (n = 260) or AD (n = 509) patients and controls (n = 438 and n = 428, respectively). 8 Higher dementia risk observed in those with a higher 24-OHC/27-OHC ratio is in agreement with the marginally significant findings of increased cognitive impairment risk reported by Hughes et al, but, in contrast, we did not observe a relationship between 24-OHC levels and dementia risk in our exclusively female sample. 45 Nonetheless, our study is the first to report significantly greater dementia risk in relation to higher 24-OHC/27-OHC, and specifically in APOE3 and APOE4+ carriers.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, our study is the first to report significantly greater dementia risk in relation to higher 24‐OHC/27‐OHC, and specifically in APOE 3 and APOE 4+ carriers. While this finding could reflect a protective effect of a higher 24‐OHC/27‐OHC ratio against dementia among APOE 2+ carriers, the consistent reports of the deleterious effects of altered oxysterol levels 6–10,16,17,21–24 suggest a greater likelihood that APOE ε2 allele may instead be protective against pathological effects of abnormal oxysterol levels. Nevertheless, this interaction between oxysterols and APOE in relation to cognitive impairment should be interpreted with caution given the small number of cases among APOE 2+ carriers.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…With regard to diabetes mellitus, nutritional supplementation with redox bioactive compounds was proposed to prevent or ameliorate muscle loss (Lee et al 2022) and the improvement of mitochondrial function outlined as one of the primary targets of this syndrome's treatment (de Marañón et al 2022). Of interest in the neuropsychiatric field are the systematic check of the literature concerning the actual applicability of measuring defined oxysterols as markers of Alzheimer's disease (Ademowo and Dias 2022), and the reviews on the pathophysiological role of the redox-regulated protein DJ-1 in Parkinson's disease and other pathologies (Dash et al 2022), the potential therapeutic use of sirtuins in the treatment of Rett syndrome (Cordone et al 2022), an appropriate insight into the mechanisms by which hypoxic preconditioning actually attenuates neuronal oxidative stress and damage was afforded (Millán et al 2022). Finally, the impact of a major oxysterol of non-enzymatic origin, namely 7-ketocholesterol, in human pathophysiology, as well as in food science, was comprehensively examined (Ghzaiel et al 2022) and the essential role of selenium as a micronutrient, but also its toxicity at non physiological amounts, has been fully reported on by Saito (2022).…”
mentioning
confidence: 99%